2022
DOI: 10.1002/jemt.24065
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for post‐traumatic stress disorder identification utilizing resting‐state functional magnetic resonance imaging

Abstract: Early detection of post-traumatic stress disorder (PTSD) is essential for proper treatment of the patients to recover from this disorder. The aligned purpose of this study was to investigate the performance deviations in regions of interest (ROI) of PTSD than the healthy brain regions, to assess interregional functional connectivity and applications of machine learning techniques to identify PTSD and healthy control using resting-state functional magnetic resonance imaging (rs-fMRI). The rs-fMRI data of 10 ROI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Depression leads to somatic problems, mental disorders, sleep disorders, and gastrointestinal problems. The self-confidence and rumination symptoms show in depression-related patients [ 3 , 4 ]. It affects the functioning or performance of patients at school, family, and work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression leads to somatic problems, mental disorders, sleep disorders, and gastrointestinal problems. The self-confidence and rumination symptoms show in depression-related patients [ 3 , 4 ]. It affects the functioning or performance of patients at school, family, and work.…”
Section: Introductionmentioning
confidence: 99%
“…e selfcon dence and rumination symptoms show in depressionrelated patients [3,4]. It a ects the functioning or performance of patients at school, family, and work.…”
Section: Introductionmentioning
confidence: 99%
“…Medial prefrontal cortex, amygdala, thalamus, hippocampus, and precuneus were chosen as the region of interests (ROIs) and compared the functional connections among them in another study. Saba T et al [ 21 ] tested five machine learning algorithms and discovered that SVM had the greatest classification accuracy of 99.2%. The author concluded that this will identify the best algorithm for providing identification recommendations.…”
Section: Resultsmentioning
confidence: 99%
“…These methods mostly had AUCs of 0.75-0.96, ranging in accuracy from 57.58% to 92.5% [45][46][47][48] . MRI techniques, such as fMRI and DTI, combined with machine learning have been used in the prediction, diagnosis, and assessment of PTSD [49,50] . However, machine learning models based on conventional MRI radiomics for PTSD diagnosis have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [57] used the combination of multi-level features extracted from fMRI images and multi-kernel learning to classify PTSD cases and healthy controls with an accuracy of 92.5%. Saba et al [49] used machine learning combined with rs-fMRI to classify PTSD cases and healthy controls with an accuracy of 93.7-99.2% (K-nearest neighbor and SVM with radial basis function kernel) in the training, validation, and test groups. This study had a lower diagnostic performance than previous clinical studies due to the following reasons: differences in the types of trauma, assessment methods, demographic characteristics of participants, MRI techniques, brain region selection, or machine learning algorithms.…”
Section: Discussionmentioning
confidence: 99%